Description Of The Strategy Of Students In Utilizing Traditional Games As Support Of The Learning Process - M.Kes, Supriyono S.KM; Irawati, Erni (Universitas Muhammadiyah Kalimantan Timur, 2022)
Abstract. Background. As one of the cultural assets, traditional games must be preserved and developed by the millennial generation, it should be guarded not to just disappear, in this archipelago, as a result of advances in science and technology. Objective. To get an overview of the facilitator a strategy in utilizing traditional games to support the Learning Process. The method in this research is through a survey using the google form application. The sample is all widyaiswara throughout Indonesia, with inclusion criteria willing to fill in the form on the google form with the link: https://forms.gle/8FQw9WMtJJejUVej9. The number of respondents was 72 people. The collected data is then processed through the process of collecting, editing, coding, then presented in a frequency table. The results of the study, obtained the following information, the average age of the respondents was 51.58 years, the sex of the respondents was predominantly male, reaching 55.60%, with most of the education levels being postgraduate. Meanwhile, most of the functional positions of the state civil servants are Associate Expert Widyaiswara, the largest is Jakarta 22.22%, Central Java 19.44% and West Nusa Tenggara. 9.72%. Based on teaching experience, it was found that 34.70% of respondents had taught material using traditional game media, and as many as 90.30% of respondents agreed if traditional games were involved in colouring the learning process. conclusion, most of the widyaiswara agree that traditional games are included in the teaching and learning process to enrich learning methods. Widyaiswara's concern for traditional games is quite high. The philosophy contained in traditional games is to teach cooperation, cohesiveness, tolerance, hard work, honesty, discipline, never giving up, disciplinary unity, never giving up, brotherhood Keywords: Strategy, Lecturer, Traditional Games, Learning Process